Preliminary evidence of softwood shortage and hardwood availability in EU regions: A spatial analysis using the European Forest Industry Database - Bozzolan, Nicola; Mohren, Frits; Grassi, Giacomo; Schelhaas, Mart-Jan; Staritsky, Igor; Stern, Tobias; Peltoniemi, Mikko; Šebeň, Vladimír; Hassegawa, Mariana; Verkerk, Pieter Johannes; Patacca, Marco; Jansons, Aris; et al. (Elsevier, 2024)
As the overall demand for wood-based products continues to grow, questions arise on how local wood resources and industry characteristics can effectively meet this growing demand. In the European Union (EU) 550 million m3 of wood is harvested annually, and is to a large extent processed by the wood industry. Little is known about the interplay between industrial capacity and the regional availability of timber resources. We compared the capacities from the European Forest Industry Facilities Database (EUFID) with the estimated wood supply from the procurement areas around processing industries, calculated using a spatially explicit resource model (EFISCEN-Space). We found that the estimated total capacity for the available European countries is 427 M m3 roundwood equivalent (rw. Eq.) for pulp and paper (including both virgin and recycled fibres), 102 M m3 for bioenergy (only bioenergy plants), and 153 M m3 for sawmills. We then conducted an in-depth analysis of three case studies: Norway, the Czech Republic, and Germany. Given the current probability of trees being harvested (excluding disturbances) and the hypothetical optimal grading of the logs, the volume for each assortment type is closely aligned with the current capacity of each industry branch, indicating no overcapacity. We found undersupply of softwood of 3.4 M m3 for the Czech Republic, 1.5 M m3 for Norway, and 3.8 M m3 for Germany. At the same time, in Germany, we found an oversupply of hardwood of 3.0 M m3. Additionally, a substantial amount of biomass graded as bioenergy was found for Germany and the Czech Republic, potentially serving as fuelwood in households. Concerning wood procurement areas, we concluded that a fixed radius of 100 km from the facility limited the availability of raw material procurement, particularly for bioenergy and pulp and paper mills, suggesting that these two product chains use a broader procurement basin than sawlogs. This study provides a high-resolution, spatially explicit modelling methodology for assessing the interaction between potential wood harvest and industrial processing capacity, which can support projections of sustainable development of the forest industry.
Keywords: wood allocation; wood grading; pulp and paper industry; sawmill industry; forest sector models